Towards trans-diagnostic mechanisms in psychiatry: neurobehavioral profile of rats with a loss-of-function point mutation in the dopamine transporter gene - Vengeliene, Valentina; Noori, Hamid Reza; Bartsch, Dusan; Schneider, Miriam; Schloss, Patrick; Spanagel, Rainer (Disease models & mechanisms, 2017)
The research domain criteria (RDoC) matrix has been developed to reorient psychiatric research towards measurable behavioral dimensions and underlying mechanisms. Here, we used a new genetic rat model with a loss-of-function point mutation in the dopamine transporter (DAT) gene (Slc6a3_N157K) to systematically study the RDoC matrix. First, we examined the impact of the Slc6a3_N157K mutation on monoaminergic signaling. We then performed behavioral tests representing each of the five RDoC domains: negative and positive valence systems, cognitive, social and arousal/regulatory systems. The use of RDoC may be particularly helpful for drug development. We studied the effects of a novel pharmacological approach metabotropic glutamate receptor mGluR2/3 antagonism, in DAT mutants in a comparative way with standard medications. Loss of DAT functionality in mutant rats not only elevated subcortical extracellular dopamine concentration but also altered the balance of monoaminergic transmission. DAT mutant rats showed deficits in all five RDoC domains. Thus, mutant rats failed to show conditioned fear responses, were anhedonic, were unable to learn stimulus-reward associations, showed impaired cognition and social behavior, and were hyperactive. Hyperactivity in mutant rats was reduced by amphetamine and atomoxetine, which are well-established medications to reduce hyperactivity in humans. The mGluR2/3 antagonist LY341495 also normalized hyperactivity in DAT mutant rats without affecting extracellular dopamine levels. We systematically characterized an altered dopamine system within the context of the RDoC matrix and studied mGluR2/3 antagonism as a new pharmacological strategy to treat mental disorders with underlying subcortical dopaminergic hyperactivity.